International Year of Planet Earth 9. Geology in the Urban Environment in Canada - Karrow, P.; Clague, John (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2010)
SUMMARY Over 80% of Canadians are urban dwellers, and geology plays a major role in their living environment. Aggregates, water supply, waste disposal, and building problems associated with compressible or sensitive sediments, swelling clays, and dense tills, are major urban geological concerns. A variety of geological hazards impact our cities, including earthquakes, tsunami, volcanic eruptions, landslides, flooding and, along the Pacific and Atlantic coasts, sea level rise. New urban challenges arise from declining reserves of fossil fuels and global climate change, both of which require a rapid transition to alternative energy sources (wind, solar, geothermal) and rebuilt infrastructure. Canada will increasingly face urban issues that require enhanced public education and the services of geologists.